Proceedings of the Seventh International Symposium on Ground Support in Mining and Underground Construction 2013
DOI: 10.36487/acg_rep/1304_11_villaescusa
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic testing of welded and woven mesh for rock support

Abstract: The Western Australian School of Mines has designed, commissioned and extensively used testing facilities capable of subjecting panels of steel wire mesh to static and dynamic loadings. Since commissioning, a large number of tests have been performed on mesh with different wires diameters and apertures. The forcedisplacement responses of the mesh have been measured and then characterised by various performance indicators such as rupture strength, displacement to rupture and energy absorption. The database of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Tannant et al 1997) had bolts and plates installed at the corners of the test sheet, similar to what is installed in underground conditions. From published documents (see Villaescusa et al 2013b), WASM considered there was a need for consistent boundary conditions that could be replicated in both their static and dynamic test setups. They reasoned that full size mesh panels were too large to test in their laboratory setup, and that the cut down panels which could be tested needed some restraint beyond just the four bolts at the corners.…”
Section: Western Australia School Of Mines Static Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tannant et al 1997) had bolts and plates installed at the corners of the test sheet, similar to what is installed in underground conditions. From published documents (see Villaescusa et al 2013b), WASM considered there was a need for consistent boundary conditions that could be replicated in both their static and dynamic test setups. They reasoned that full size mesh panels were too large to test in their laboratory setup, and that the cut down panels which could be tested needed some restraint beyond just the four bolts at the corners.…”
Section: Western Australia School Of Mines Static Facilitymentioning
confidence: 99%
“…The WASM dynamic facility uses a similar setup to the WASM static facility (Figure 1) but with a drop weight that transfers the load onto the mesh (Figure 9). Loading is done via a 0.5 or 1.0 t bag of steel balls with a 0.65 × 0.65m contact area to the mesh, delivering 3.8 to 16.1 kJ input energy to the central 25% area of the mesh sheet (Villaescusa et al 2013b). The mesh panel size (1.3 × 1.3 m) and rigid mesh boundary (fixed via shackles to the frame) are the same as used for the static configuration.…”
Section: Western Australia School Of Mines Dynamic Facilitymentioning
confidence: 99%
“…Weak links occur for a multitude of reasons, and a common experience is mesh tearing away from bolt collars. Western Australian School of Mines testing (Villaescusa et al 2013) of numerous meshes has shown that most mesh surface support types have capacity much less than that of the bolt reinforcement system. The exceptions are the high strength chain link meshes.…”
Section: Scheme Capacity Is Affected By Weak Linksmentioning
confidence: 99%
“…The ultimate tensile strength and strain of many steels is relatively insensitive to strain rate up to a value of, at least, 10 s -1 and, in general, these values slightly increase with strain rate (Soroushian & Choi 1987). This material behaviour is observed by comparing quasi-static and dynamic rupture loads and displacements of standard welded-wire and chain-link mesh tested in the laboratory (Player et al 2008;Villaescusa et al 2012).…”
Section: Introductionmentioning
confidence: 99%